Applying mechanical equilibrium rules in project cost management. (June 2016) - Bagherpour, Morteza; Safari, Mojtaba; Mohammad Sharifi, Masoud
The earned value management is a systematic approach to measure project progress and forecast final cost of a project. However, this method has not significantly been improved over its earlier version and there are some criticisms against this standard method. This approach presents a good condition if only the cost performance index shows satisfactory results. The objective of this research is to propose a new methodology in project financial system according to the rules and regulations on mechanical equilibrium of a beam. The results have been successfully implemented which improved the standard project cost management system.